Working women of the Bible : timeless mentors for modern women - DiMickele, Susan M. (Abilene, Texas : Leafwood Publishers, 2013)
As working women struggle to find mentors in today's society, Working Women of the Bible asks, what if the women of Scripture are the very mentors we ve been looking for? Most working women today understand they can never be Superwoman. But if Superwoman is unattainable, whom are we trying to emulate? Is the Bible completely outdated, or does it offer a blueprint, full of real-life, culturally relevant examples for the twenty-first century working woman? Can we actually find female mentors in the Bible--women who defied cultural norms and held positions of power and influence?
Eve: the trailblazer -- Rahab: second chances -- Deborah: a time to lead -- Ruth: embracing plan C -- Jezebel: the ultimate power trip -- Huldah: building a solid reputation -- Widow in debt: giving what we have -- Esther: embracing our destiny -- Proverbs 31: can we have it all? -- Mary: moving toward the pain -- Martha -- Lydia: finding your own style -- Priscilla -- Jesus.
Includes bibliographical references.
Description based on print version record.
Keywords: Women in the Bible; Women -- Employment; Women -- Employment; Women in the Bible; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books